NANOPARTICLES: A PROMISING DRUG DELIVERY APPROACH - Kadian, Renu (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â  Â Nanoparticles are particles having a size range of 1 and 100 nanometers, defined as a small object behaving as a complete unit with respect to the drug transport and therapeutic properties. They have several advantages such as improvement in the intracellular infiltration, enhanced hydrophobic solubility, and circulation time of the drug. They reduce non-specific uptake and side effects of the conventional drug delivery systems. Nanoparticles offer more effective and convenient routes of administration (oral, pulmonary, parenteral, and transdermal) and used for drug delivery for treatment of cancer, diabetes, pain, asthma, allergy, infections, and so on. They allow targeted delivery and controlled release of the drug. Further research on their mechanism of action to meet better stability of nanoparticles in the biological system could be done.